Phospholipase C-related but Catalytically Inactive Protein Is Required for Insulin-induced Cell Surface Expression of γ-Aminobutyric Acid Type A Receptors - Fujii, Makoto (American Society for Biochemistry and Molecular Biology, 2010)
The γ-aminobutyric acid type A (GABA(A)) receptors play a pivotal role in fast synaptic inhibition in the central nervous system. One of the key factors for determining synaptic strength is the number of receptors on the postsynaptic membrane, which is maintained by the balance between cell surface insertion and endocytosis of the receptors. In this study, we investigated whether phospholipase C-related but catalytically inactive protein (PRIP) is involved in insulin-induced GABA(A) receptor insertion. Insulin potentiated the GABA-induced Cl(−) current (I(GABA)) by about 30% in wild-type neurons, but not in PRIP1 and PRIP2 double-knock-out (DKO) neurons, suggesting that PRIP is involved in insulin-induced potentiation. The phosphorylation level of the GABA(A) receptor β-subunit was increased by about 30% in the wild-type neurons but not in the mutant neurons, which were similar to the changes observed in I(GABA). We also revealed that PRIP recruited active Akt to the GABA(A) receptors by forming a ternary complex under insulin stimulation. The disruption of the binding between PRIP and the GABA(A) receptor β-subunit by PRIP interference peptide attenuated the insulin potentiation of I(GABA). Taken together, these results suggest that PRIP is involved in insulin-induced GABA(A) receptor insertion by recruiting active Akt to the receptor complex.